EXAMINING ADHD IN PUPILS: ADDRESSING OBSTACLES TO LEARNING - Nabi, Asima (Trinity College (Dublin, Ireland). School of Education, 2022)
There are many misunderstandings about the condition labelled ADHD experienced by some children in schools. Parents in Kashmir believe that their children have an inferiority complex or are afflicted by foul spirits or demons and/or badly behaved, therefore the need to become more educated about ADHD is important. The rationale for this study is to explore more about special educators’ knowledge and experience in examining ADHD in pupils and addressing their learning barriers in their classrooms. For data collection and interpretation, this study used a phenomenological approach. The study included ten participants from two different special schools. The researcher conducted one-on-one interviews using a semi-structured interview format. Purposive sampling and open-ended questions were used. The findings show that children with ADHD may have a variety of academic and social problems and that teachers’ and parents’ assistance, understanding, and awareness are key factors in helping children with ADHD achieve positive outcomes. Keywords: Attention -Deficit Hyperactivity Disorder (ADHD), Special education
Keywords: Special Need Education; Education